Hybrid Model Approach for Impulsive Noise Removal Image Enhancement Techniques - Verm, Pratima; Kurmi, Jitendra (International Journal of Computer Sciences and Engineering, 2025)
In the world of digital image processing, image enhancements is a biggest challenge without losing any information of image, better visualization, edge prevention and provide better quality of the image etc. At the time of image processing, images are corrupted by different types of noises. Using noise removal techniques we have remove noises from the digital image. In this paper we discussed about the impulsive noise and techniques for removal of impulsive noise from digital image by proposed algorithm. The proposed algorithm “An Approach for Hybrid Impulsive Noise Image Enhancement Techniques” is a combination of two algorithms Modified Decision Based Unsymmertic Trimmed Median filter (MDBUTMF) and Fast Switching Based Median Filter for high Density Salt and Pepper noise (FSBMMF). It gives better Peak-Signal-to-Noise Ratio (PSNR) and Image Enhancement Factor (IEF).